ANALISIS PRODUK DIGITAL SANTRI SEBAGAI MEDIA DAKWAH PONDOK PESANTREN SUNAN DRAJAT LAMONGAN DALAM MENSYIARKAN NILAI-NILAI KEISLAMAN - Nashihin; Dwi Ahmad Syahrul Munir (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
In this millennial era, technology has become a tool where people use it as reference material, especially on the internet. The internet as a medium for distributing information has now become almost a reference for all people, especially Indonesian people. Sometimes information that is not necessarily true is disseminated. One of the digital technologies currently developing is social media. In its use, social media can be used as a medium for preaching in the modern era. This research aims to: Find out the concept of Santri Digital Products as a da'wah medium for the Sunan Drajat Lamongan Islamic Boarding School in broadcasting Islamic values and to find out the da'wah messages contained. This research uses a descriptive qualitative approach to describe Santri Digital Products as Da'wah Media for the Sunan Drajat Lamongan Islamic Boarding School in Broadcasting Islamic Values, by means of data collection techniques, analyzing data, interviews, observations in terms of the daily life experiences of the subjects studied. The results of this research are the concept of digital santri products, namely preaching using digital santri products, namely audio-visual content which is the same as the characteristics of digital products, namely that they do not have a physical form, can be accessed anywhere, are easily changed and updated, and are available in various forms. with different features. Apart from that, the concept of da'wah displayed is the selection of material, the use of relatively relaxed language, and explaining the benefits and advantages.